Original Russian probiotic Acipol: molecular-biologic and metabolic characteristics - N. Yu. Ivashkina; S. G. Botina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
Aim of investigation. To study molecular-biologic and metabolic properties of agent «Acipol» with account to modern requirements to probiotic drugs.Materials and methods. To study quality properties of Acipol investigation of strains of the agent by polymerase chain reaction (PCR) of DNA amplification and sequenation of 16S RNA gene of NK1, NK2, NK5, NK12 strains of L. acidophilus was carried out. At ultracentrifugation of bacterial cells with further electrophoretic separation and visualization of extrachromosomal fraction in agarose gel absence of mobile genomic information was found. Metabolic properties of Acipol strains were studied by standard biochemical and microbiologic procedures.Results. The original study proved specific belonging of NK1, NK2, NK5, NK12 strains of L. acidophilus at genetic level, ability of strains to synthesize exopolysaccharides, to tolerate low pH values and influence of bile. Properties of lactobacilli to produce vitamins, to suppress proliferation of saprophytic microflora, as well as metronidazole-resistance properties were revealed.Conclusions. The complex assessment of Acipol testifies to its conformity to the up-to-date requirements to biological preparations.